Doctrina social de la iglesia e inclusión universitaria - Díaz Flores, Segundo Artidoro (2012)
The present article talks about the difficulties of the university inclusion ofwhat is consider part of the problem to the resistance from certain sectorsto accept all types of students, with or without special needs. Faced withthis problem, the author considers that the principles and values of theSocial Doctrine of the Church constitute an ethical and moral reference forthat the university inclusion become in a reality of higher education.